Integrating Atmospheric Sensors into Unmanned Aerial Systems - Cleary, Patricia Anne; Nelson, Aaron; Stout, Alex (My University, 2017)
Analyzing atmospheric conditions in situ using manned airplanes has historically been effective and limiting. With the growing usage of UAS, this project is aimed at incorporating atmospheric sensors into a UAS as a viable, inexpensive and responsive method for atmospheric monitoring. Our group's goal is to record serial data from a compac ozone monitor connected to a Raspberry Pi.
Color poster with text, charts, and images.
Keywords: Flight data; Atmospheric sensors; Aerial systems; Posters